Evaluating hydrogen production from glucose using graphite felt beads as a solid matrix in immobilized mixed cell reactor at thermophilic fermentation - Ssatar, Ibdal; Salehmin, Mohd Nur Ikhmal; Abu Bakar, Mimi Hani; Wan Daud, Wan Ramli; Kumalasari, Ika Dyah; Aziz, Muhammad; Somalu, Mahendara Rao; Kim, Byung Hong (Communications in Science and Technology, 2023)
This study has successfully evaluated graphite felt (GF) beads as a solid matrix to immobilize or trap the mixed cultures in an immobilized mixed-cell reactor (IMcR). The anaerobic sludge of palm oil mill effluent was used as an inoculum source in the IMcR with mixed culture. Here, glucose, sucrose, and starch were used as the model substrates to evaluate the performance of IMcR with GF beads for producing bio-hydrogen (BioH2). BioH2, effluent, and surface morphology of GF beads were analyzed by using gas chromatography equipped with a thermal conductivity detector, high-performance liquid chromatography, and scanning electron microscopy, respectively. The highest H2 yield (YH2) and production rates were obtained at 304.0 ± 13.2 mL g?1COD (corresponding to 2.26 mol mol?1glucose) and 1403 ± 61 mL L?1 day?1, respectively. IMcR with GF beads is a new approach for generating high YH2, which can be used for more than two months in an experimental run.